Modulation of Astrocytic Glutamine Synthetase by Endocannabinoid 2-Arachidonoylglycerol in JNK-Independent Pathway - Wang, Jing; Wang, Shenghong; Zhang, Hua (Frontiers in Pain Research, 2021)
Background and Objective: The glutamine synthetase (GS), an astrocyte-specific enzyme, plays an important role in neuroprotection through the glutamate/glutamine shuttle and can be modulated by endocannabinoid (eCB) 2-arachidonoylglycerol (2-AG) through extracellular signal-regulated protein kinase ½ (ERK1/2) and p38 signaling pathways. However, the role of c-Jun N-terminal kinase (JNK) signaling pathway in the modulation of GS in astrocytes by 2-AG is not clear. Materials and Methods: The expression of GS and JNK in astrocytes following the exposure to lipopolysaccharide (LPS) was examined with Western blotting and immunochemistry. Results: The results revealed that short-term exposure to LPS activated GS and increased phosphorylation of JNK in astrocytes in a time-dependent manner. Treatment with 2-AG reversed the changes in GS but had no effect on the activation of JNK. Conclusions: These findings suggest that the activation of JNK induced by LPS is not involved in the modulation of astrocytic GS by 2-AG.